DDX10 and BYSL as the potential targets of chondrosarcoma and glioma. Issue 46 (19th November 2021) - Quan, Xuemin; Zhao, Changsong; Gao, Zhengrong; Zhang, Yao; Zhao, Rugang; Wang, Jingjing; Zhang, Qiang
Abstract : Abstract: To provide reliable molecular markers and effective therapeutic targets for chondrosarcoma and glioma. Gene Set Enrichment (GSE) 29745 and GSE48420 were downloaded from the Gene Expression Omnibus (GEO) database. Differently expressed genes (DEGs) were identified by the GEO2R. We annotated the function of common DEGs through Digital Audio/Video Interactive Decoder (DAVID) and Metascape. Protein–protein interaction network construction was performed through STRING. Hub genes were identified by the two different algorithms (MCC, EPC). DDX10 and BYSL were key factors in embryo implantation and development, and plays a role in a variety of cancers. The role of the DDX10 and BYSL on the glioma derived from the chondrosarcoma would be explored by the clinical samples. A total of 1442 DEGs were identified. The variations in DEGs were mainly enriched in vasculature development, cell motion, blood vessel development, cell migration, regulation of cell proliferation, regulation of cell proliferation, wound healing, biological adhesion, growth factor binding, identical pathways in cancer, and p53 signaling pathway. Dead-box helicase 10 (DDX10), Bystin-like (BYSL), and WD repeat domain 12 (WDR12) were identified as the hub genes, and the three hub genes were up-regulated in the chondrosarcoma. Chondrosarcoma patients with high expression levels of DDX10 (Logrank P = .0052; HR (high) = 1.8; n (high) = 131, 50%), and BYSL ( P = 6.5e-05; HR (high) = 2.3; n (high) = 131, 50%) had poorer overall survival times than those with low expression levels. DDX10 and BYSL genes may provide reliable molecular markers and effective therapeutic targets for chondrosarcoma and glioma.